Patients with systemic lupus erythematosus show a normal responsive search score in exploratory eye movement analysis: comparison with schizophrenia. Issue 8 (1st August 2002) - Matsukawa, Y; Takahashi, S; Aoki, M; Yamakami, K; Nishinarita, S; Horie, T; Fukura, Y; Tanabe, E; Yara, K; Matsuura, M; Kojima, T
Abstract : Objective: To assess whether a difference in psychiatric vulnerability exists between patients with systemic lupus erythematosus (SLE) and those with schizophrenia. Methods: Twenty women with SLE underwent exploratory eye movement analysis, and a responsive search score (RSS) was obtained, two months after the onset of the disease. Fifteen women with schizophrenia in remission also underwent this analysis. Exploratory eye movement was recorded by an eye mark recorder, which detects corneal reflection of infrared light. The number of eye fixations (instance of more than 0.2 seconds of eye fixation time) was recorded, and the RSS was calculated from eye fixation analysis. Results: Mean (SD) RSS differed significantly between patients with SLE and those with schizophrenia (9.85 (1.87) v 7.27 (1.58) points, respectively, p<0.0001), whereas no difference in mean RSS was found between patients with SLE and 19 normal women. No difference in mean RSS was found between patients with active SLE and those with inactive SLE (9.51 (1.87) v 10.0 (1.77) points). Conclusion: The psychiatric vulnerability in patients with SLE, measured by the RSS, differs from that in patients with schizophrenia.